Bank Supervision and Corporate Credit Supply - Ivanov, Ivan T.; Wang, James Z. (Management Science, 2024)
We exploit the quasi-random assignment of federal bank examiners to syndicated loans to study the effect of supervision on corporate lending. Following supervisory rating downgrades, banks decrease credit commitments and downgrade internal risk assessments. Borrowers face larger commitment reductions whenever banks have low ex ante screening and monitoring incentives or whenever examiners’ assessments contain more information than banks’ assessments, suggesting that examinations complement bank monitoring. Although public firms can offset the loss of bank credit by tapping external capital markets, smaller and more opaque private firms draw on internal cash balances instead and reduce investment and sales growth. This paper was accepted by Victoria Ivashina, finance. Supplemental Material: The data files are available at https://doi.org/10.1287/mnsc.2023.4854 .